Change agent behavior and organizational effectiveness of the Rajabhat Institutes in Bangkok, Thailand - Sirisukcharoenporn, Thitikorn (Vigan City : [s.n.], 2002)
This study aimed to determine the level of change agent behavior and organizational effectiveness of the Rajabhat Institutes in Bangkok, Thailand. It also looked into the personal profile of the administrators, faculty and non-teaching staff in terms of age, sex, civil status, educational attainment, length of service, present position/designation and number of training/seminars attended, The respondents were limited to 281 administrators, 1,194 faculty and 309 non-teaching staff of the six Rajabhat Institutes of Bangkok, Thailand during the school year 2001-2002 The questionnaire used to gather the data on change agent's behavior and organizational effectiveness was adopted from Pungsri (1992). The descriptive-correlational method of research was used in the study with a survey questionnaire in gathering the needed data and information. Weighted mean, standard deviation, t-test, analysis of variance and simple correlational analysis were used in statistically treating the gathered data. Findings had shown that on the personal characteristics of the respondents (administrators, faculty and non-teaching staff), there was a great number of males (1,124 or 63,01%) whose age range from 31-40 years old, and married. Many had finished bachelor's degree with advanced Masteral units; had been in the service for 21-30 years, were mere instructors, and attended seminars/training in the local/institutional level. The level of change agent behavior of the administrators, faculty and non- teaching staff was generally a "Somewhat a Characteristic" rating While the level of organizational effectiveness of these three respondents had varied ratings At any rate, the "Agree" descriptive rating dominated, but some were rated as "Undecided" Analysis of variance showed insignificant differences on the change agent behavior among the administrators, faculty and non-teaching staff of the Rajabhat Institutes in Bangkok, Thailand. This was evidenced by the computed F ratio o .05, which is very much lower than the tabular F value of 3.55. On the other hand, the organizational effectiveness on awareness showed significant difference between the faculty and the non-teaching staff with a t-value of 1.86. In flexibility, insignificant difference was displayed. And in productivity, it also revealed insignificant result as shown by the computed F-value of 1.62, which is lower than the tabular F-value of 3,55. The personal characteristics of the respondents in terms of educational attainment, length of service and present position or designation were significantly related to change agent behavior as shown by the computed t-values of 23.42, 3.0 and 10.12, respectively. Meanwhile, the personal circumstances on age, civil status. length of service and position yielded significant relationship with organizational effectiveness. As a conclusion, the three groups of respondents possessed the minimum standard qualifications that warrant their position. Their level of change agent behavior manifested good value for they had assessed it as "Somewhat a Characteristic" and their level of organizational effectiveness showed a low outcome for it has revealed varied ratings The level of the behavior of the three groups of respondents relative to their functions as change agent was comparable The level of organizational effectiveness between the faculty and the non-teaching staff of the Rajabhat Institutes in Bangkok, Thailand in relation to awareness differed significantly of incomparable. This was due to the fact that they vary in their functions Educational attainment, length of service and present position of the respondents were significantly related to change agent behavior. This showed that there is a great influence of their behavior towards their tasks as change agents of the institute. Only age, civil status, length of service and position manifested significant relationship to organizational effectiveness. This revealed that older, married, longer in the service and those with administrative functions were expected to acquire higher level of organizational effectiveness. As for the recommendation, aspiration for the maximum qualification is highly suggested for the respondents by attending further studies and seminars. There must be deepening sessions for all the workers of the institutes even only twice in a school year regarding on how to become a change agent. The administrators must reassess also the status of the institutes' organizational effectiveness by their workers and themselves.
Bibliography: pages 71-73.
CHED-La Union
Keywords: Higher education